PELATIHAN BAHASA INGGRIS UNTUK SISWA KELAS 5 SEKOLAH DASAR NO 2 PENGIANGAN DENGAN METODE ROLE PLAY - Dewa Made Agustawan; Ida Ayu Gede Sasrani Widyastuti; Ni Luh Ayu Cempaka Dewi (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
Abstract: English language training for elementary school students is one way to improve basic communication skills in a foreign language from an early age. This study was conducted to explore the role-play method in teaching English to elementary school students, which aims to create an interactive, enjoyable, and student centred learning environment. Through this method, students are given the opportunity to act out various simple situations frequently encountered in everyday life, such as introducing oneself, greeting, asking and giving information, and shopping conversations. The training was carried out in stages through the provision of vocabulary, example dialogues, group exercises, and role-playing in front of the class. The training results showed that the role-play method was able to increase students' confidence in speaking English, enrich vocabulary mastery, and improve pronunciation and understanding of the context of language use. In addition, students showed high enthusiasm and participation throughout the activity. Thus, the role-play method can be an effective learning alternative to support the development of English language skills in elementary school students. Keywords: English language training, elementary school, role play   Abstrak: Pelatihan bahasa Inggris bagi siswa sekolah dasar merupakan salah satu upaya untuk meningkatkan kemampuan komunikasi dasar dalam bahasa asing sejak usia dini. Penelitian ini dilaksanakan untuk mengksplorasi metode role play dalam mengajar bahasa Inggris bagi siswa sekolah dasar yang bertujuan menciptakan suasana belajar yang interaktif, menyenangkan, dan berpusat pada siswa. Melalui metode ini, siswa diberikan kesempatan untuk memerankan berbagai situasi sederhana yang sering ditemui dalam kehidupan sehari-hari, seperti introducing oneself, greeting, asking and giving information, dan shopping conversation. Pelatihan dilaksanakan secara bertahap melalui pemberian kosakata, contoh dialog, latihan kelompok, dan penampilan peran di depan kelas. Hasil pelatihan menunjukkan bahwa metode role play mampu meningkatkan kepercayaan diri siswa dalam berbicara bahasa Inggris, memperkaya penguasaan kosakata, serta meningkatkan kemampuan pelafalan dan pemahaman konteks penggunaan bahasa. Selain itu, siswa menunjukkan antusiasme dan partisipasi yang tinggi selama kegiatan berlangsung. Dengan demikian, metode role play dapat menjadi alternatif pembelajaran yang efektif untuk mendukung pengembangan keterampilan berbahasa Inggris pada siswa sekolah dasar. Kata kunci: pelatihan bahasa Inggris, sekolah dasar, role play.